The Yusuf trilogy. [part 2], Süt [videorecording (DVD)] - Kaplanoğlu, Semih, 1963-; Köklükaya, Başak; Selçuk, Melih; Akın, Rıza (Olive Films, 2011)
Recent high school graduate Yusuf is uncertain about his future in the provincial countryside. Writing poetry is his greatest passion and some of his poems are starting to be published in obscure literary journals. But for the time being, he continues working in his single mother's village milk business. Since her husband's death, Yusuf's widowed mother has focused all her attention to her only child. Still a young and beautiful woman, she is having a relationship with the town stationmaster.